Empowering the Future: The Vision of Smart Transmission Grids - Amit Kumar Kolhe; Dr. Vijaylaxmi Biradar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In the quest for an adaptable, dependable, and sustainable energy supply, the modern power grid necessitates a transformative upgrade towards intelligence. While substantial efforts have been devoted to envisioning and advancing smart power grids in the United States and Europe, the focus has predominantly centered on the distribution grid and demand-side management, leaving the holistic perspective of the transmission grid within the context of smart grids somewhat obscured. This paper proposes a distinct vision for the future of smart transmission grids, delineating their pivotal attributes. In this envisioned framework, each smart transmission grid emerges as a cohesive, integrated system comprising three interrelated smart components: smart control centers, smart transmission networks, and smart substations. The paper meticulously outlines the characteristics and functionalities of each of these three essential components, elucidating the enabling technologies necessary to realize their envisioned capabilities. By conceptualizing smart transmission grids as multifaceted systems driven by intelligent components, this vision underscores the potential for enhancing grid efficiency, reliability, and sustainability. Through the seamless integration of advanced control centers, transmission networks, and substations empowered by cutting-edge technologies, smart transmission grids aim to optimize grid operations, facilitate dynamic energy management, and foster resilience against emerging challenges and disruptions.
Keywords: Cutting-Edge Technologies; Smart Transmission Grids; Control Centers